Siyāsah Sharʿiyyah and State Governance in Zakat Management: A Case Analysis of Judicial Review on BAZNAS Authority vis-à-vis LAZ/BAZ Institutions - R. Zaari, Ali Rajeh R. Zaari; Hasibuan, Elmira; Rifadilla, Wahyu; R. Jasin, Muhammad (Graduate School of UIN Syarif Hidayatullah Jakarta, 2025)
Law No. 38/1999 established Indonesia’s first legal framework for zakat management, institutionalizing the National Zakat Agency (BAZNAS) and civil society-led Amil Zakat Institutions (LAZ). Revised through Law No. 23/2011 to enhance oversight and systemic integration, the amendment triggered debates over four critical issues: (1) potential criminalization of LAZ/BAZ (Articles 38-41); (2) centralization of authority under BAZNAS; (3) operational restrictions on LAZ/BAZ (Article 20); and (4) legal ambiguities and perceived inequities. This study examines state regulatory roles in zakat governance through Constitutional Court Case 97/PUU-XXII/2024, which challenges BAZNAS’s exclusive authority. Using normative juridical methods, the paper analyzes statutory frameworks and LAZ’s legal arguments against Law 23/2011. Findings reveal tensions between centralized state control and civil society autonomy, underscoring unresolved legal ambiguities in Indonesia’s zakat ecosystem. The research contributes to discourse on balancing regulatory efficiency with participatory governance in Islamic social finance systems.